2014
DOI: 10.1166/jnn.2014.9561
|View full text |Cite
|
Sign up to set email alerts
|

Metal Oxide Coated Lithium Cobalt Fluorophosphate Cathode Materials for Lithium Secondary Batteries—Effect of Aging and Temperature

Abstract: Lithium cobalt fluorophosphate (Li2CoPO4F) is a promising 5 V class cathode material for lithium secondary batteries. In this study, surface coating with ZrO2 improved the electrochemical activity of Li2CoPO4F with a maximum discharge capacity of 144 mA h g(-1). The effectiveness of ZrO2 coating was evaluated using aging analysis with a commercial electrolyte, i.e., 1 M LiPF6 in EC:DMC (1:1, v/v). The metal ion dissolution was reduced to 1/8th of that observed in the non-coated Li2CoPO4F. It was found that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, recent studies have indicated that Li 2 CoPO 4 F can reach a maximum reversible capacity of 150 mA h g −1 , with an outstanding high-voltage operation of ~5 V vs. Li +  /Li111527282930. Because of the high inefficiency from the first to the second cycle observable in Li 2 CoPO 4 F, these electrodes were subjected to activation cycles before being used in the complete lithium-ion cell (see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, recent studies have indicated that Li 2 CoPO 4 F can reach a maximum reversible capacity of 150 mA h g −1 , with an outstanding high-voltage operation of ~5 V vs. Li +  /Li111527282930. Because of the high inefficiency from the first to the second cycle observable in Li 2 CoPO 4 F, these electrodes were subjected to activation cycles before being used in the complete lithium-ion cell (see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[114][115][116] Moreover, surface coatings onto cathode material with oxides (NiO or MnO 2 ) can essentially shield from direct exposure to the electrolyte solution, improving the structural integrity of the cathode material and suppressing phase transitions. 117,118 For the supercapacitors, a conducting polymer such as polypyrrole (PPy) usually is used to coat the surface of the electrode materials to, which lead to signicantly improved electron transport within every nanostructures. PPy was chosen not only because it has greater density and better degree of exibility, but also itself can undergo a fast redox reaction to store charge.…”
Section: Surface Coatingmentioning
confidence: 99%